The Effectiveness of Village Fund Management in Village Development Based on Law Number 6 of 2014 Concerning Villages - Siprianus Gano (Jurnal Restorasi : Hukum dan Politik, 2023)
The effectiveness of handling village funds pursuant to Law Number 6 of 2014 on Villages' phases and objectives can be assessed. Village development in accordance with laws can solve many local difficulties. The village government and community must work together to develop. How well does village financial management accomplish village development in Ruis Village, Reok District, Manggarai Regency, (2) What hinders village finance management in Ruis Village, Reok District, Manggarai Regency village development. This empirical legal research employs site data. We employ primary and secondary legal materials. We employed qualitative descriptive analysis.According to the study, village fund management effectiveness in Ruis Village, Reok District, Manggarai Regency, is less effective during implementation. The government should give community socialization and village development information. Engages communities in village development. A village financial accountability report should detail the results of work with Ruis Village people over a specific period since the phases of accountability are inefficient. (2) Poor human resources, facilities, and infrastructure limit village finance administration in Ruis Village, Reok District, Manggarai Regency. The government should prioritize money management stages with development planning and give training and help.